A Teaching Environment that Favors Learning. A Study at the University of Atacama Faculty of Engineering - Gonzalez Maura, Viviana Lázara (2019)
The article reveals the results of a descriptive study about the teaching-learning environment of a representative sample of second-year students at the Faculty of Engineering at the University of Atacama (UDA). We elaborated a teaching environment scale that favors student learning consisting of 12 variables and 60 indicators [referred to as ECEFAE]. The main purpose was to evaluate the extent to which the teaching-learning process corresponds to features of student-centered teaching from a student perspective. Our results show that the current teaching environment does not sufficiently favor learning. On average, autonomous learning received the highest scores followed by organization and discipline and cooperative learning. Learning assessment, environmental conditions and linkages between theory and professional activities had the worst scores. The study validates the methodological value of the [ECEFAE] technique for diagnosing teaching-learning environments and identifies factors that favor or hinder the transition towards a student-centered approach to teaching for second-year Engineering students at UDA. The conclusions reinforce the need to compare teacher and student views as well as combine quantitative and qualitative techniques in classroom environment studies for a greater understanding of this diagnosis. The results of this study have been taken into account for designing teacher-training courses.